Some Vector FK Sequence Spaces Generated by Modulus Function - Herawati, E.; N. Irsyad; E. Rosmaini (Journal of Research in Mathematics Trends and Technology, 2020)
In this paper, some vector valued sequence spaces and using modulus function are presented. Furthermore, we examined some topological properties of these sequence spaces equipped with a paranorm.